Green areas state assessment within the urban territories - Shestopalov, Oleksii; Tykhomyrova, Tetyana; Lebedev, Volodymyr; Stadnik, Veronika (Scientific Route OÜ, 2022)
The urbanized environment is a complex heterogeneous system that is constantly changing. In large cities, there is a complex stress effect on living organisms. Different areas of the city may be permanently or temporarily dominated by a cer tain stress factor. Vegetation is a component of urban landscapes, which are natural and artificial objects of various functional purposes. The ecological functions of green spaces include: environmental protection, environmental regulation and aesthetic functions. All these functions play an important role within residential buildings, especially in children’s playgrounds. Various types of damage to green spaces negatively affect their main functions. The susceptibility to damage of woody plants by insects depends on anthropogenic factors of the environment, which lead to the weakening of plants and to the loss of resistance to these types of negative influences. The resistance of plants to diseases often decreases under the influence of transport and industrial pollution in the external environment. The purpose of the study is phytopathological analysis of the green areas state on children’s playgrounds in Kharkiv. Green plantations state assessment methods of urban areas using various technical means are analyzed. Green plantings condition and morbidity analysis using one of the offered methods is carried out. Accord ing to the results of phytopathological analysis, it was determined that 100 % of the species Aesculus hippocastanum L., which grow on playgrounds in Kharkiv, are affected by Cameraria ohridella. Among the bushes, Syringa vulgaris L. and Spiraea L. are the most affected by diseases and pests.
Keywords: phytopathological analysis; GIS; playgrounds; urban territories; green spaces; monitoring methods; TreeTalker; WebGIS system; chlorosis; іnsects-phytophagous